PERANCANGAN DAN ANALISA CIRCULAR POLARITY ANTENNA CROSSHAIR WAVEGUIDE SEBAGAI PENGUAT WIFI ADAPTER TP-LINK TL-WN723N PADA FREKUENSI 2,4 GHZ - ., Yulianus Sandi (Jurnal Teknik Elektro Universitas Tanjungpura, 2016)
Abstrak  - Waveguide  Crosshair Antenna   with   reflectors   which   has   the function to change the radiation pattern and beam width antenna beam so that in itself could increase the antenna gain. The amount of  change  in  the  gain  generated  by  the addition of the reflector can be affected by several things, among them is to set the size of the  reflector  panel  angle  (α),  adjust  the amount of spacing between the driven element and reflector panel (space), and change the length dimension of the reflector (h). The resulting radiation pattern     waveguide Crosshair antenna is directional, the signal emitted in two directions with the same magnitude.  With  the  addition  of  reflectors, will limit the radiation pattern from being widened backward and transmits force will be strengthened in the opposite direction, so that one  can  clearly  see  how  it  changes  the transmit antenna patterns before and after the addition  of  the  reflector,  the  antenna amplifier is more devoted to the working frequency of 2.4 GHz for wireless LAN ( local area network ). The parameters that must be considered in designing antennas for wireless LAN is working frequency. To test the speed of the download (download) and upload (upload), conducted through speedtest.net on two different networks, namely network UNTAN hotspot network in the faculty of engineering with download speeds of 72.23 Mbps, 50.56 Mbps upload network and the Faculty  of  Engineering  at  the  speed  3.05 Mbps download, upload 2.13 Mbps, which is influenced by the speed  speedtest maximum value and minimum speed provided by the ISP (internet Service Provider). Kata kunci: Crosshair Waveguide Antenna, External Antenna, Wifi Adapter frekuensi 2.4 GHz